2019
DOI: 10.1111/bjd.18540
|View full text |Cite
|
Sign up to set email alerts
|

The sentinel node biopsy has not come of age

Abstract: Linked Article: McGregor et al. Br J Dermatol 2019; 181:423.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…4 Sentinel lymph node biopsy status (SLNBS) might contribute only a marginal survival predictability above that of an algorithm of CAPP. 5,6 Until recently, no quality research has been available to test this hypothesis.…”
Section: Improved Methodology In Determining Melanoma Mortality and S...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Sentinel lymph node biopsy status (SLNBS) might contribute only a marginal survival predictability above that of an algorithm of CAPP. 5,6 Until recently, no quality research has been available to test this hypothesis.…”
Section: Improved Methodology In Determining Melanoma Mortality and S...mentioning
confidence: 99%
“…4 Sentinel lymph node biopsy status (SLNBS) might contribute only a marginal survival predictability above that of an algorithm of CAPP. 5,6 Until recently, no quality research has been available to test this hypothesis.El Sharouni et al (ESS) 7 recently detailed the prognostic value of CAPP, with or without SLNBS, for calculating overall survival (OS) for melanoma patients. Predictors including Breslow thickness, tumour, ulceration, patient age, sex, mitotic activity, regression, tumour subtype and location were evaluated in 9272 Dutch patients.…”
mentioning
confidence: 99%
“…Some clinicians have been cautious about or have disagreed with claims made about the role of SLNB in melanoma management. In particular, there has been disagreement over the claimed survival benefit and the prognostic benefit of SLNB over and above other readily available clinicopathological criteria of the primary melanoma 12–15 . Rates of SLNB in Australia and internationally have been reported to be between 33% and 53% 16–20 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there has been disagreement over the claimed survival benefit and the prognostic benefit of SLNB over and above other readily available clinicopathological criteria of the primary melanoma. [12][13][14][15] Rates of SLNB in Australia and internationally have been reported to be between 33% and 53%. [16][17][18][19][20] A recent study reported the views of Australian general practitioners towards SLNB, 21 but there are limited data on Australian dermatologists' knowledge of and attitudes towards SLNB in the management of melanoma.…”
Section: Introductionmentioning
confidence: 99%